Solve `7=b-4` :

We can add equal numbers to both sides of an equation (the addition property of equality): in this case add 4 to both sides to get:

`7+4=b` or `11=b` . We can then use the symmetric property of equality to rewrite as :

`b=11`

--------------------------------------------------------

**Thus if `7=b-4` then `b=11` **

-------------------------------------------------------

Solve `a+5=-8` :

Here we can use the addtion property of equality again; this time adding -5 to both sides to get:

`a+5-5=-8-5` or `a=-13`

-------------------------------------------------------

**Thus if `a+5=-8` then `a=-13` **

------------------------------------------------------

7=b-4 just combine like terms by adding or subtracting

7+4=b

11=b so b=11

a+5=-8

a=-8-5

a=-13

7 = b - 4 and a + 5 = -8

First let's solve " b "

7 = b - 4 now add 4 on both sides

By adding 4 on both sides , you should get

11 = b which is your answer for " b "

Now let's solve for " a "

a + 5 = -8 subtract 5 on both sides

By subtracting 5 on both sides , you should get

a = -13 which is yours answer for " a "

So " a " is -13 and " b " is 11

7 = b - 4

To get the variable b by itself, we have to negate the -4. We add 4 to both sides:

7 + 4 = b - 4 + 4

11 = b

We do the same thing for the next one .

a+5=-8

To get the variable a by itself, we have to negate the +5. We subtract 5 from both sides:

a + 5 - 5 = -8 - 5

a = -13